The Behavior Of Food Handlers On The Use Of Food Packaging In Restraurants In Mamuju District, Mamuju Regency - Hairuddin, Miftah Chairani; Adiningsih, Ridhayani; Magfirah; Rahmah, Siti (Jurnal Sanitasi Profesional Indonesia, 2023)
Packaging today often uses plastic and Styrofoam as food packaging. The current packaging can endanger consumers, food contamination due to the use of Styrofoam can occur due to the following ; food or drink that is too hot, the higher the temperature of the food in the styrofoam, the easier it will be for the styrene substance to transfer to the food. Ths study aims to determine the behavior of handlers towards the use of food packaging in restaurants in Mamuju District of Mamuju Regency. The sample in this study were 127 restaurant handlers. The results showed that the level of knowledge of food handlers in the less category was 59,1%, the attitude of food handlers was in the positive category by 37,8% and 62,2% had a negative attidue, the actions of handlerswere 40,9% had a positive attitude and 59,1% had a negative attitude. The number of restaurants handlers was 127 handlers interviewed, 62,2% had a negative attitude and as many as 37,8% positive attitude. This study concluded that the attitude of respondents was in a negative category towards the use of food packaging as a food and beverage container, because the attitude of the handler was not only formed by the knowledge of the handler but was also influenced by the emotional aspects, experience, and environtmental conditions the handlers was in. conclusion the description of the knowledge, attitudes and actions of handlers towards the use of food packaging in restaurants in Mamuju District, Mamuju Regency is in less category based on the results of the study.